Analisa Beberapa Sifat Fisikokimia dari Minyak Goreng Kemasan Hasil Penggorengan dengan Lemak Sapi - Rahmi, Fathaniah Raviqa; Hardeli, Hardeli; Nasra, Edi; Pernadi, Niza Lian; Sabrina, Joya; Farhan, Muhammad; Nizar, Umar Kalmar (Departemen Kimia FMIPA UNP, 2024)
Palm oil is one of the vegetable oils with the highest concentration of contaminants compared to other oils. The main components of palm oil are triglycerides which account for more than 95% and other components such as monoglycerides, diglycerides, free fatty acids, phosphatides and sterols. Beef in 100 grams contains fewer calories (498 kj), total fat (2.8 g), unsaturated fat (0.448 g), saturated fat (1.149 g) and cholesterol (50 mg) than goat meat of the same size .The nutritional composition of beef includes 18.8 grams of protein, 66.0 grams of water and 14.0 grams of fat. The aim of this research is to determine the physicochemical properties of packaged cooking oil produced from frying beef fat at certain temperatures and times. The physicochemical properties of the oil determined include density, flow rate, acidity index and saponification index. Bimoli cooking oil resulting from the frying process has a density value of 0.9205 gr/ml, a flow rate of 2.949 ml/s, an acid number of 3.06939 mgKOH/gr and a saponification index of 16.71005 mgKOH/gr. The results of this research indicate that the results of testing the physicochemical properties of packaged cooking oil have better values compared to the results of testing beef tallow cooking oil.